A possible role of the norepinephrine system during sequential cognitive flexibility – Evidence from EEG and pupil diameter data. (July 2020) - Giller, Franziska; Mückschel, Moritz; Ziemssen, Tjalf; Beste, Christian
Abstract: Sequential cognitive flexibility is a major requirement for goal-directed behavior. Recent findings show that inhibitory control processes are crucial for sequential cognitive flexibility. These processes are indicated by the 'backward inhibition (BI) effect' which emerges when a mental representation that has recently been suppressed in favour of another task has to be re-activated. Alterations in the catecholaminergic neural transmission including the norepinephrine (NE) system have been shown to modulate inhibitory processes. However, a possible role of the NE system in sequential cognitive flexibility is elusive. The present study examines the relevance of the NE system for sequential cognitive flexibility by integrating pupil diameter data and electrophysiological (EEG) data applying signal decomposition techniques and source localization. We show that the BI effects modulated amplitudes in the P1/N1 time window, as well as in the N2 time window. Correlating this data with the pupil diameter data only revealed substantial correlations in the P1/N1 time window. Moreover, it is shown that regions in the right inferior frontal gyrus are activated during modulations in the P1 time window, in which correlations with the pupil diameter data were also evident. The results are interpreted that sequential cognitive flexibility modulates early inhibitory gating processes (P1) which are related to the suppression of task-irrelevant information in inferior frontal regions. These processes are likely modulated by the NE system.